Extending the Limits of the Abatement Cost - Guy Meunier; Jean-Pierre Ponssard (Center for Economic Studies and ifo Institute (CESifo), 2022)
The paper examines the relevant cost benefit framework for public authorities investigating the potential of local projects to mitigate climate change. Because these projects are typically limited in time and space, continuation pathways need be introduced to capture the benefits provided by a project over the longer term. This issue is particularly acute in the transition toward carbon neutrality, which aims for the full abatement of emissions by a future end date. The relevant question is not whether or not to decarbonize an activity but when to do so, and how. We propose a new metric that incorporates into the analytical framework the dynamic interactions between a project and its continuation. This metric is defined as the annual overall discounted cost divided by the long term annual abatement. The new metric is a non trivial extension of the standard cost of abatement. It determines when precisely to launch a given project and addresses the question of how to compare competing projects using their on going emissions up to their respective optimal launch dates. Two illustrations make clear the novelty of our approach: the choice of the optimal mix of technologies for the electricity sector and the comparison between competing green technologies for mobility.
Keywords: Q51; Q56; R58; 330; cost benefit analysis; abatement cost; time value of money; learning-by-doing